Heterogeneous Two‐Phase Pillars in Epitaxial NiFe2O4‐LaFeO3 Nanocomposites. Issue 16 (10th July 2017) - Comes, Ryan B.; Perea, Daniel E.; Spurgeon, Steven R.
Abstract : Self‐assembled epitaxial oxide nanocomposites have been explored for a wide range of applications, including multiferroic and magnetoelectric properties, plasmonics, and catalysis. These so‐called "vertically aligned nanocomposites" form spontaneously during the deposition process when segregation into two phases is energetically favorable as compared to a solid solution. However, there has been surprisingly little work understanding the driving forces that govern the synthesis of these materials, which can include point defect energetics, surface diffusion, and interfacial energies. To explore these factors, La‐Ni‐Fe‐O films have been synthesized by molecular beam epitaxy and it is shown that these phase segregate into spinel‐perovskite nanocomposites. Using complementary scanning transmission electron microscopy and atom‐probe tomography, the elemental composition of each phase is examined and found that Ni ions are exclusively found in the spinel phase. From correlative analysis, a model for the relative favorability of the Ni 2+ and Ni 3+ valences under the growth conditions is developed. It is shown that multidimensional characterization techniques provide previously unobserved insight into the growth process and complex driving forces for phase segregation. Abstract : Self‐assembled epitaxial oxide nanocomposites have been explored for a wide range of applications, but there has been surprisingly little work understanding the driving forces that govern the synthesis of these materials. Using complementary electron microscopy and atom‐probe tomography to examine the atomic‐scale structure of these materials, this work addresses fundamental questions on the driving forces for formation of vertically aligned nanocomposites.